Immune Phenotyping of Patients With Acute Vogt-Koyanagi-Harada Syndrome Before and After Glucocorticoids Therapy - Jiang, Han; Li, Zhaohui; Yu, Long; Zhang, Ying; Zhou, Li; Wu, Jianhua; Yuan, Jing; Han, Mengyao; Xu, Tao; He, Junwen; Wang, Shan; Yu, Chengfeng; et al. (Frontiers in Immunology, 2021)
Previous studies have established that disturbed lymphocytes are involved in the pathogenesis of Vogt-Koyanagi-Harada (VKH) syndrome. Accordingly, glucocorticoids (GCs), with their well-recognized immune-suppressive function, have been widely used for treatment of VKH patients with acute relapses. However, the systemic response of diverse immune cells to GC therapy in VKH is poorly characterized. To address this issue, we analyzed immune cell subpopulations and their phenotype, as well as cytokine profiles in peripheral blood from VKH patients (n=25) and health controls (HCs, n=21) by flow cytometry and luminex technique, respectively. For 16 patients underwent GC therapy (methylprednisolone, MP), the aforementioned measurements as well as the transcriptome data from patients before and after one-week’s GC therapy were also compared to interrogate the systemic immune response to GC therapy. Lymphocyte composition in the blood was different in VKH patients and HCs. VKH patients had significantly higher numbers of T cells with more activated, polarized and differentiated phenotype, more unswitched memory B cells and monocytes, as compared to HCs. MP treatment resulted in decreased frequencies of T cells and NK cells, inhibited NK cell activation and T cell differentiation, and more profoundly, a marked shift of monocytes toward an anti-inflammatory phenotype. Collectively, our findings suggest that advanced activation and differentiation, as well as dysregulated numbers of peripheral lymphocytes are the major immunological features of VKH, and GC therapy with MP not only inhibits T cell activation directly, but also affects monocyte subsets and polarizes monocyte toward a suppressive phenotype, endowing them with the capacity to inhibit the pathogenic immune response.